Pembuatan Sabun Cuci Tangan dalam Peran Serta Penanganan Covid-19 Berdasarkan Peraturan Menteri Kesehatan Nomor 62 Tahun 2017 Bersama PCM Kramat Jati dan Pemuda Muhammadiyah Kramat Jati Jakarta Timur – DKI Jakarta - Marjan Miharja; Wiend Sakti Myharto; Valentino Brostito; Hasan Hasan; Muhammad Sofyan Hidayat; Yulius Alfredo; Emilio Raynaldi Porwayla; Novariyadi Putra Ardhana (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
The spread of Covid-19 has become one of the people's concerns, starting in the city of Wuhan, China at the end of 2019 when this virus was discovered, the spread of the virus that the antidote has not yet been found is now out of control. More than 200 countries in the world have reported that their people have contracted the Covid-19 virus. Corona Virus Disease 19 has been declared a Global Public Health Emergency by the World Health Organization (WHO) on January 30, 2020. Conditions in Indonesia until Thursday, November 30, 2020, the number of people who tested positive for Covid-19 reached 538,883 cases, 450,518 people recovered and 16,945 of them died. This figure will continue to increase in line with the opinion of some epidemiologists and statistics that a pandemic outbreak will not end quickly. The purpose of this community service activity is to realize one of the contents of the Minister of Health Regulation No. 62 of 2017, namely